Notes on genera of Sarimini with description of two new species in the genera Microsarimodes and Tetrichina (Hemiptera: Fulgoromorpha: Issidae) - Wang, Menglin; Zhang, Yalin; Bourgoin, Thierry (Zootaxa, 2020)
Two new species of the tribe Sarimini in the planthopper family Issidae: Microsarimodes flavomaculata sp. nov. and Tetrichina fuscovinclum sp. nov. are described from China. The genera Duplexissus Wang, Zhang & Bourgoin, 2019 and Sarimissus Wang, Zhang & Bourgoin, 2019 are reestablished as valid genera based on both morphological grounds and molecular analyses.